2018
DOI: 10.1111/lam.13048
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular maltotriose hydrolysis bySaccharomyces cerevisiaecells lacking theAGT1permease

Abstract: Maltotriose is the second most abundant sugar present in brewing. However, many yeast strains have difficulties to consume maltotriose, mainly because of its low uptake rate by the yeast cells when compared to glucose and maltose uptake. The AGT1 permease is required for efficient maltotriose fermentation, but some strains deleted in this gene are still able to grow on maltotriose after an extensive lag phase. This manuscript shows that such delayed growth on maltotriose is a consequence of extracellular hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…It has previously been assumed that transport of maltotriose into the yeast cells is required for it to be consumed during wort fermentations (Day et al 2002; Rautio and Londesborough 2003; Alves et al 2008), but our results suggest that extracellular hydrolysis of maltotriose through STA1 allows for efficient consumption of maltotriose from the wort throughout fermentation. A recent study also reported extracellular hydrolysis of maltotriose by an α-glucosidase encoded by IMA5 (Alves et al 2018); however, in that case, maltotriose hydrolysis was only observed after an extensive lag phase. In brewing yeast where maltotriose use is enabled through the AGT1 -encoded transporter , maltotriose is typically consumed from the wort only towards the later parts of fermentation when maltose concentrations are low (Rautio and Londesborough 2003).…”
Section: Discussionmentioning
confidence: 97%
“…It has previously been assumed that transport of maltotriose into the yeast cells is required for it to be consumed during wort fermentations (Day et al 2002; Rautio and Londesborough 2003; Alves et al 2008), but our results suggest that extracellular hydrolysis of maltotriose through STA1 allows for efficient consumption of maltotriose from the wort throughout fermentation. A recent study also reported extracellular hydrolysis of maltotriose by an α-glucosidase encoded by IMA5 (Alves et al 2018); however, in that case, maltotriose hydrolysis was only observed after an extensive lag phase. In brewing yeast where maltotriose use is enabled through the AGT1 -encoded transporter , maltotriose is typically consumed from the wort only towards the later parts of fermentation when maltose concentrations are low (Rautio and Londesborough 2003).…”
Section: Discussionmentioning
confidence: 97%
“…The underlying reason for this molecule to be involved in the control of a complex important regulon is likely because it is a marker of the ecological niche of E. coli . To be sure, maltotriose is abundant in mixtures that result from incomplete fermentation of plant seed mixtures [this accounts for Saccharomyces cerevisiae being unable to ferment maltotriose efficiently (Alves et al ., )]. Maltotriose is thus expected to be present as a major catabolic by‐product of carbohydrate fibres in the gut of many mammals, where E. coli thrives (van Zanten et al ., ).…”
Section: An Open List Of Basic Cellular Maxwell's Demonsmentioning
confidence: 99%
“…Strain CAT-1 has the AGT1 gene in chromosome VII [ 76 ], but this strain does not efficiently ferment maltotriose (another substrate of the AGT1 permease) [ 44 ] due to the presence of a divergent and non-functional promoter region, also found in other industrial yeast strains unable to ferment maltotriose [ 77 ]. Instead, strain CAT-1 uses maltotriose only after an extensive lag phase, and it metabolizes this sugar aerobically due to its extracellular hydrolysis mediated by the isomaltase encoded by the IMA5 gene [ 44 , 78 ]. Indeed, as can be seen in Table 3 , strain CAT-1 had no p NPαG transport activity, a measurement of this permease’s activity, indicating that it was also necessary to overexpress the AGT1 gene.…”
Section: Resultsmentioning
confidence: 99%